KOLABORASI ANTAR STAKEHOLDER DALAM MENGEMBANGKAN PASAR RAKYAT PAYUNGI KOTA METRO - Fadri Ari Sandi; Yusup Lintang Cahyo Andrian Putro; Rafika Afriyanti; Helni Sadid Parassa; Agus Priyanto (Journal Publicuho, 2025)
This study aims to map the potential and creative space generated by the community and map the roles and collaboration between stakeholders in developing the Payungi People's Market. The research uses a descriptive qualitative approach with primary and secondary data obtained through in-depth interviews, field observations, and document analysis. The research results show that collaboration among stakeholders plays a key role. The Payungi movers became the main driving force in organizing activities, the private sector supported through funding and marketing, the government provided policy facilitation, universities assisted through research and mentoring, and the community became the main actors in market activities. The strategies implemented include empowering the local community, community-based promotion, and strengthening networks among stakeholders. However, the main challenges faced include the regeneration of community mobilizers and the low level of technology adoption by market players, especially mothers. This research emphasizes the importance of synergy among stakeholders in creating an inclusive, sustainable, and competitive creative economy space. These findings provide practical guidance for the development of similar markets in other regions.